2015
DOI: 10.4236/ajps.2015.612196
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for Artificial MicroRNA Mediated Over-Expression of miR820 in Indica Rice

Abstract: In the present study, we illustrate the strategy and protocol required to generate rice transgenics over-expressing the 21-nt form of Osa-miR820. The miR exists in two size variants of 21-nt and 24-nt so the natural precursor cannot be employed for the purpose of miR over-expression as the cellular machinery can process both size variants thereby masking the role of PTGS regulation. Hence, we adopted the artificial miR technology to specifically over-express the 21-nt species in the transgenics. During the cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…S5b-d), so that same amiRNA construct can also be used against other begomoviruses. The three designed amiRNAs (Table 1) were amplified by four sets of primers ( Supplementary Table S3) via overlapping PCR on the pNW55 vector backbone for obtaining pre-miRNA as given in Sharma et al 53 . The pre-amiRNA fragment was then cloned in pRT101, using XhoI and BamHI sites for directional cloning, under CaMV-35S promoter.…”
Section: Detection and Confirmation Of Rss Activitymentioning
confidence: 99%
“…S5b-d), so that same amiRNA construct can also be used against other begomoviruses. The three designed amiRNAs (Table 1) were amplified by four sets of primers ( Supplementary Table S3) via overlapping PCR on the pNW55 vector backbone for obtaining pre-miRNA as given in Sharma et al 53 . The pre-amiRNA fragment was then cloned in pRT101, using XhoI and BamHI sites for directional cloning, under CaMV-35S promoter.…”
Section: Detection and Confirmation Of Rss Activitymentioning
confidence: 99%
“…Another study revealed that the overexpression of the osa-miR7695 resulted in enhanced disease resistance to the fungal pathogen Magnaporthe oryzae , the cause of rice blast disease (Campo et al, 2013 ). Another recent study reported that Osa-miR820 plays a role in salt, high temperature, and drought stress responses (Sharma et al, 2015a ).…”
Section: Functional Roles Of Mirnasmentioning
confidence: 99%
“…Therefore, artificial miR based strategy was adopted to specifically over-express the 21-nt length variants. The Osa-miR820 overexpressing transgenic lines (OX-820) were generated and confirmed, as described earlier [40].…”
Section: Resultsmentioning
confidence: 99%
“…The regulatory role of this miR on DRM2 transcripts was evident and the narrow windows of transcript regulation were captured. For gaining further insights into the biological significance of 21-nt species of Osa-miR820 in rice, artificial miR based over-expressing transgenic lines, OX-820 were generated [40]. In the present work, we report the phenotype and physiology of OX-820 under normal and saline conditions.…”
Section: Introductionmentioning
confidence: 99%